Ginsenosides Rg1, Rb1 and rare ginsenosides: Promising candidate agents for Parkinson's disease and Alzheimer's disease and network pharmacology analysis - Mingchun Jiang; Jiaxin Chi; Yifan Qiao; Jinpeng Wang; Zhixin Zhang; Jia Liu; Xinhao Sheng; Liangjie Yuan (Pharmacological Research)
Ginseng has been commonly used as a traditional Chinese medicine in Asian countries for thousands of years. Ginsenosides are the main pharmacologically active ingredients isolated from ginseng and have neuroprotective effects in the treatment of neurodegenerative disorders, such as Parkinson's disease (PD) and Alzheimer's disease (AD). To summarise and investigate the protective roles of ginsenosides and their underlying mechanisms in PD and AD, we used ‘‘Ginsenoside”, ‘‘Parkinson's disease”, ‘‘Alzheimer's disease”, ‘‘anti-inflammatory”, ‘‘antioxidant”, and ‘‘apoptosis” as keywords to search and extract relevant literature information from scientific databases such as Elsevier, PubMed, and Google Scholar databases. In particular, we used network pharmacology to identify the potential targets of ginsenosides Rg1 and Rb1 in PD and AD. By analysing the existing research advances and network pharmacology results, we found that the neuroprotective effects of ginsenosides, primarily mediated through anti-inflammation, anti-apoptosis and anti-oxidative stress, etc, may be associated with the PI3K/Akt, BDNF/TrkB, MAPKs, NF-κB, Nrf2 and Wnt/β-catenin signalling pathways. This review systematically summarises the different roles and mechanisms of ginsenosides Rg1, Rb1, and rare ginsenosides in PD and AD and provides new strategies for the treatment of neurodegenerative disorders. Network pharmacology provides a new research paradigm for the treatment of PD and AD using Rg1 and Rb1.